2002
DOI: 10.1016/s0304-3959(01)00429-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical hyperalgesia after an L5 ventral rhizotomy or an L5 ganglionectomy in the rat

Abstract: An L5 spinal nerve ligation (SNL) in the rat leads to behavioral signs of mechanical hyperalgesia. Our recent finding that an L5 dorsal root rhizotomy did not alter the mechanical hyperalgesia following an L5 SNL suggests that signals originating from the proximal stump of the injured nerve are not essential. We postulate that Wallerian degeneration of L5 nerve fibers leads to altered properties of adjacent intact nociceptive afferents. To investigate the role of degeneration in sensory versus motor fibers, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 78 publications
3
52
2
2
Order By: Relevance
“…Furthermore, others reported that L5 dorsal rhizotomy did not attenuate L5 SNL-induced mechanical allodynia and that L5 dorsal rhizotomy itself can lead to pain behaviors (Colburn et al, 1999;Tabo et al, 1999;Eschenfelder et al, 2000;Li et al, 2000;Sheth et al, 2002). Therefore, various methodological factors, such as the type of injury, the extent of the lesion, the distance of the injury from the DRG, time courses, and behavioral testing techniques, may contribute to the discrepancy between our observations and those of others.…”
Section: Mapk Activation In the Injured L5 Drg Neurons And Mechanicalcontrasting
confidence: 91%
“…Furthermore, others reported that L5 dorsal rhizotomy did not attenuate L5 SNL-induced mechanical allodynia and that L5 dorsal rhizotomy itself can lead to pain behaviors (Colburn et al, 1999;Tabo et al, 1999;Eschenfelder et al, 2000;Li et al, 2000;Sheth et al, 2002). Therefore, various methodological factors, such as the type of injury, the extent of the lesion, the distance of the injury from the DRG, time courses, and behavioral testing techniques, may contribute to the discrepancy between our observations and those of others.…”
Section: Mapk Activation In the Injured L5 Drg Neurons And Mechanicalcontrasting
confidence: 91%
“…The other two plantar nerve branches demonstrated myelinated fiber loss reflecting the relative contribution of L5 axons to those nerves: the middle plantar nerve was modestly affected, and the medial plantar nerve was minimally affected. These experiments were conducted in parallel to behavioral and electrophysiological studies on the effects of L5 ventral rhizotomy that were reported previously (Sheth et al, 2002;Wu et al, 2002). The spontaneous behavior of the animals in this study, e.g., mild weakness of hindlimb flexion, matched that seen in the parallel studies.…”
Section: Resultssupporting
confidence: 57%
“…Experimental manipulations used in pain research include transection of the mixed spinal nerve, dorsal root ganglionectomy, chronic constriction injury of the nerve, and ventral rhizotomy (Kim and Chung, 1992;Munger et al, 1992;Sheth et al, 2002). In each of these models, some of the axons in the peripheral nerve are undergoing Wallerian degeneration, whereas other axons remain intact.…”
Section: Remak Schwann Cells Do Not Measurably Increase In Numbersmentioning
confidence: 99%
“…In contrast, the role of ventral root injury is rarely considered as a contributor to the development of neuropathic pain. There is recent evidence which suggests, however, that a unilateral L5 ventral root transection (VRT) in rats is sufficient to induce hyperalgesia (i.e., a reduced pain threshold for nociceptive stimuli) and allodynia (i.e., a normally innocuous stimulus is perceived as painful) , Sheth et al, 2002, Obata et al, 2004. Thus, a direct injury to the sensory afferents may not be necessary to induce the development of neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%